Carbon sequestration of the poikilohydric moss carpet vegetation in semidesert sandy grassland ecosystem - Juhász, Anita (Acta Biologica Szegediensis, 2002)
Seasonal change in diurnal C02 exchange of the desiccation-tolerant ectohydric moss Tortula ruralis was investigated in situ to determine its contribution to C02 exchange of the carbon balance of the temperate semi-arid sandy grassland ecosystem. A hemisphere perspex chamber (20 cm in diameter) was used to measure the CO2 gas exchange of the moss cushions. Diurnal course of air temperature, surface temperature of moss carpet, and photosynthetic photon flux density were also monitored. The seasonal characteristics of the diurnal course of net C02 assimilation in T. ruralis showed strong dependence on microclimatic conditions. The highest daily carbon fixation rates were measured in December and January. In summer, the moss carpet of the community remained mainly dormant and the daily C-balance started to increase again in October. During the year the daily C-balances of T. ruralis was positive. These results demonstrate that the T. ruralis contribute significantly to the C-balance of the sandy grassland vegetation in the large of the year.